If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(y + -3) = 7 Reorder the terms: 7(-3 + y) = 7 (-3 * 7 + y * 7) = 7 (-21 + 7y) = 7 Solving -21 + 7y = 7 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '21' to each side of the equation. -21 + 21 + 7y = 7 + 21 Combine like terms: -21 + 21 = 0 0 + 7y = 7 + 21 7y = 7 + 21 Combine like terms: 7 + 21 = 28 7y = 28 Divide each side by '7'. y = 4 Simplifying y = 4
| 9c+c-6= | | 4x^2-4=2x-1 | | 1.12(c+4)=14.56 | | 1-2[4-3(x-1)]=4(x-5)-1 | | 4+x=.25(28x-8) | | 3(x-4)-67=2x+46 | | 24+4c=3c-3 | | 4x-2(x-4)=-3+5x+2 | | X-36=64 | | 8y=50 | | 10x=410 | | 42+5x=3x | | Log(2)(2x+7)=1 | | 4x+6z=8+3y | | 3(2+2)=2(3+3) | | 6x^2+3x=135 | | 4(12-8)=w-18 | | 6(h+72)=912 | | 8y=30 | | 3-4x=4+10x | | ln(x-2)+ln(x-3)=0 | | 6n^2=10+11n | | 31+14-t=40 | | 4(y+43)+132=916 | | -6.8(2x+4)-1.5(4x-6)= | | 12-6x=-42 | | 3y-80=7y | | 396=(13+12w)(17+7w) | | 2(k+61)+16=-32 | | 12-6x=42 | | 5x^2+2x-11-3x^2=8x-7 | | n^2-6n=55 |